The influence of cabotage policy on price disparity between peninsular Malaysia and Sabah - Mhd. Ruslan, Siti Marsila; Mat Ghani, Gairuzazmi; Khalid, Haniza (Faculty of Economics and Administration, University of Malaya, 2019)
The Malaysian government introduced a cabotage policy in 1980 to protect and enhance the competitiveness of the Malaysian shipping industry. The policy requires all foreign vessels to unload at Port Klang, the designated national port, after which only Malaysian-flagged vessels can carry cargo to other ports in Malaysia. The policy was criticised for creating additional freight costs to importers and for allowing domestic shippers to monopolise the market. Critics claimed that the higher rates for transhipment services were subsequently passed on to the consumers resulting in higher prices of goods and services. This study examines the influence of Malaysia’s cabotage policy on prices and competitiveness of the shipping industry in the state of Sabah. This study used stakeholders and force-field analysis to examine the influence of the cabotage policy. The stakeholder analysis identified four different stakeholder groups, examined their positions, and rate their positions on the influence of cabotage policy using force-field analysis technique. The analyses show that the cabotage policy was not the only factor causing high prices. Port conditions, efficiency, level of infrastructure, trade imbalance, and political will must also be addressed to remedy the issue.